Quality Of Service Enabled Routing For Video Streaming In Software Defined Network - Nathan, Balasubramanian (2020)
The Internet has become the point of convergence for data, voice, audio and video. It is fast becoming the preferred platform for communication and content delivery, eventually leading to the demise of conventional PSTN telephone network and terrestrial/ satellite television. Video streaming is experiencing an unprecedented growth it currently accounts for more than half the Internet traffic and is expected to reach 82% in the next 3 years. The transmission of video and other time-sensitive content uses UDP (as opposed to TCP) because this protocol improves quality of service (QoS) in terms of providing fast and efficient transmission. Various types of QoS architecture have been proposed and deployed to further improve the quality of video transmission for example, integrated service, differentiated service and multiprotocol label switching. Recently, software-defined networking (SDN), a network virtualisation architecture, has introduced the possibility of further improving QoS, especially for multidescription coded video streaming. In the current design, such videos are transmitted over a single path that can lead to deteriorated QoS. Owing to the nature of multiple description coding (MDC) videos, the descriptions of the video can be separated and sent over multiple paths by taking advantage of the SDN design and features. Existing methods do not consider the best use of error-resiliency when deciding the multipath.